NOVICE EFL TEACHERS’ PROFESSIONAL DEVELOPMENT: A NARRATIVE INQUIRY INTO MICRO-LEVEL DEVELOPMENT PROCESS - Ikrar Ikrar; Sultan Baa (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Educational researchers have made great strides in theorizing teacher professional development, though attention is still concentrated on isolated mental processes. This study therefore reports on a narrative inquiry aiming to find out micro-level development process that occurs in two novice EFL teachers and also to reveal the features of teacher’s change that appear to facilitate English language teaching and learning. A variety of data collection techniques including; narrative frame, field notes, semi-structured interview and stimulated recall interview are used to make teachers’ behavioral, attitudinal and intellectual component of micro-level development explicit. Two overarching themes that emerge in this narrative inquiry are; the route to be a good English teacher and rediscovering the passion to teach. The important key finding of this study is that the early year of teaching is sensitively crucial to EFL teachers’ micro-level development, which is characterized by a positive shift from constructive experiences and aspiration of better English language learning process to internalization of empathy, attentive and responsive manner. Another key finding of this study is that all the novice EFL teachers who spoke positively about implementing changes in their classroom practices, embraced most of the process of micro level development that occurred, based on intuition, without clear theoretical underpinning of pedagogy, and merely classroom-bound focus. However, this study contributes to the current knowledge in relation to the crucial role of three distinct patterns of PD; discontent, aspiration and without intention